Biotechnology annual review - El-Gewely, M. Rafaat (Biotechnology Annual Review., 2006)
The primary purpose of the 'Biotechnology Annual Review' is to encourage good reviews to make it easier for the reader to keep in touch with progress and applications in biotechnology.